Correlation between Dopamine Transporter Degradation and Striatocortical Network Alteration in Parkinson’s Disease - Lin, Wei-Che; Chen, Hsiu-Ling; Hsu, Tun-Wei; Hsu, Chien-Chin; Huang, Yung-Cheng; Tsai, Nai-Wen; Lu, Cheng-Hsien (Frontiers in Neurology, 2017)
The association between dopamine neuron loss and functional change in the striatocortical network was analyzed in 31 patients with Parkinson’s disease (PD) (mean disease duration 4.03 ± 4.20 years; Hoehn and Yahr [HY] stage 2.2 ± 1.2) and 37 age-matched normal control subjects. We performed 99mTc-TRODAT-1 SPECT/CT imaging to detect neuron losses and resting–state functional magnetic resonance imaging (rs-fMRI) to detect functional changes. Mean striatal dopamine transporter binding ratios were determined by region of interest analysis. The functional connectivity correlation coefficient (fc-cc) was determined in six striatal subregions, and interactions between these binding ratios and the striatocortical fc-cc values were analyzed. The PD patients had significant functional network alterations in all striatal subregions. Lower striatal dopamine transporter binding correlated significantly with lower fc-cc values in the superior medial frontal lobe and superior frontal lobe and higher fc-cc values in the cerebellum and parahippocampus. The difference in fc-cc between the ventral inferior striatum and superior medial frontal lobe was significantly correlated with increased disease duration (r=–0.533, P=0.004), higher HY stage (r=–0.431, P=0.020), and lower activities of daily living score (r=0.369, p=0.049). The correlation of fronto-striatal network changes with clinical manifestations suggests that fc-cc may serve as a surrogate marker of disease progression.